Still Fresh

Algebra Level 4

S = 1 + cos x cos x + cos 2 x cos 2 x + + cos n x cos n x S = sin x cos x + sin 2 x cos 2 x + + sin n x cos n x S = ? S=1+\frac { \cos { x } }{ \cos { x } } +\frac { \cos { 2x } }{ \cos ^{ 2 }{ x } } +\cdots+\frac { \cos { nx } }{ \cos ^{ n }{ x } } \\ { S }^{ ' }=\frac { \sin { x } }{ \cos { x } } +\frac { \sin { 2x } }{ \cos ^{ 2 }{ x } } +\cdots +\frac { \sin { nx } }{ \cos ^{ n }{ x } } \\ S=?

Use S S' to find S S .

sin ( ( n + 1 ) x ) sin x cos n + 1 ( ( n + 1 ) x ) \frac { \sin { ((n+1)x) } }{ \sin { x\cos ^{ n+1 }{ ((n+1)x) } } } None sin ( ( n + 1 ) x ) sin x cos n x \frac { \sin { ((n+1)x) } }{ \sin { x\cos ^{ n }{ x } } } sin ( ( n + 1 ) x ) sin x cos n + 1 x \frac { \sin { ((n+1)x) } }{ \sin { x\cos ^{ n+1 }{ x } } }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mohammad Hamdar
Jan 25, 2016

S + i S = 1 + cos x + i sin x cos x + cos 2 x + i sin 2 x cos 2 x + . . . . . + cos n x + i sin n x cos n x = ( e i x cos x ) 0 + ( e i x cos x ) 1 + . . . . . + ( e i x cos x ) n = 1 ( e i x cos x ) n + 1 1 e i x cos x = 1 cos ( ( n + 1 ) x ) + i sin ( ( n + 1 ) x ) cos n + 1 x i sin x cos x = 1 sin x cos n x [ sin ( ( n + 1 ) x ) + i ( cos n + 1 x cos ( ( n + 1 ) x ) ) ] S i s t h e R e a l p a r t o f S + i S a n d S i s t h e I m a g i n a r y o n e s o , S = sin ( ( n + 1 ) x ) sin x cos n x S+iS'=\\ 1+\frac { \cos { x+i\sin { x } } }{ \cos { x } } +\frac { \cos { 2x+i\sin { 2x } } }{ \cos ^{ 2 }{ x } } +.....+\frac { \cos { nx+i\sin { nx } } }{ \cos ^{ n }{ x } } \\ ={ (\frac { { e }^{ ix } }{ \cos { x } } ) }^{ 0 }+({ \frac { { e }^{ ix } }{ \cos { x } } ) }^{ 1 }+.....+({ \frac { { e }^{ ix } }{ \cos { x } } ) }^{ n }\\ =\frac { 1-{ (\frac { { e }^{ ix } }{ \cos { x } } ) }^{ n+1 } }{ 1-\frac { { e }^{ ix } }{ \cos { x } } } =\frac { 1-\frac { \cos { ((n+1)x) } +i\sin { ((n+1)x) } }{ \cos ^{ n+1 }{ x } } }{ \frac { -i\sin { x } }{ \cos { x } } } \\ =\frac { 1 }{ \sin { x\cos ^{ n }{ x } } } \left[ \sin { ((n+1)x)+i\quad (\cos ^{ n+1 }{ x-\cos { ((n+1)x)\quad ) } } } \right] \\ S\quad is\quad the\quad Real\quad part\quad of\quad S+iS'\quad and\quad S'\quad is\quad the\quad Imaginary\quad one\\ so,\quad S=\frac { \sin { ((n+1)x) } }{ \sin { x\cos ^{ n }{ x } } }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...